Ist der Fahrplan der Energiewende noch einzuhalten? - Erik Gawel; Bernd Hansjürgens; Markus Groth; Martin Faulstich; Karin Holm-Müller; Oliver Kopp; Sebastian Schröer; Hans-Jochen Luhmann (Wirtschaftsdienst, 2013)
Die Energiewende bedeutet eine Systemtransformation des gesamten Energiebereichs hin zu erneuerbaren Energien. Der Transformationsprozess ist dabei einerseits von hohen technologischen Herausforderungen begleitet. Andererseits zeigen sich aber auch zunehmend Akzeptanzprobleme in der Bevölkerung, wenn etwa die Strompreise als zu hoch empfunden werden und dies ausschließlich der Förderung der Erneuerbaren zugeschrieben wird. Die Autoren zeigen die vielen Hindernisse auf, die den Fahrplan der Energiewende ins Wanken bringen können. – – The German energy transition represents a policy-driven, sustainability-oriented restructuring of both supply- and demand-side components of the entire energy system by 2050. Whereas the development of renewable energies in the electricity sector is right on track, due to the feed-in tariffs of the German Renewable Energy Sources Act, many other crucial requirements for a successful transition are not, amongst others the improvement of energy efficiency and the decarbonisation of the transport sector. Contrary to the public discussion, the primary future challenges do not consist in limiting electricity prices or abandoning feed-in support schemes, but rather in coordinating the variety of actors as well as appropriately matching the different system elements (grids, technologies, energy sectors, demand and supply side, etc.). Much remains to be done. By highlighting some examples like the need to take into account future implications of climate change for the energy sector, the consequences of the current crisis in the European Union's emissions trading scheme and the need for a cautious adjustment of the EEG, the paper argues that the major challenges regarding the German energy transition mainly go beyond the current policy-driven and short-term discussion of energy prices. Germany's pioneering attempt to integrate steadily increasing share of non-dispatchable electricity from renewable sources is challenging the stability of the system. Several characteristics in the current selfregulating system are identified and analysed, which reveal themselves as potential weaknesses or shortcomings in the upcoming system.
Keywords: L52; Q42; Q48; R58; 330; Förderung regenerativer Energien; Strukturwandel; Energiepreis; Öffentliche Meinung; Energieversorgung; Deutschland